2020
DOI: 10.1111/mec.15737
|View full text |Cite
|
Sign up to set email alerts
|

The complex genomic basis of rapid convergent adaptation to pesticides across continents in a fungal plant pathogen

Abstract: Convergent evolution leads to identical phenotypic traits in different species or populations. Convergence can be driven by standing variation allowing selection to favor identical alleles in parallel or the same mutations can arise independently. However, the molecular basis of such convergent adaptation remains often poorly resolved.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Further studies on larger population are needed to verify the consistency of this finding. Understanding the evolutionary pressure of environmental fungicides also on clinical isolates may allow to better decipher the mechanisms leading to fungicide adaptation [41]. This can lead to set the most appropriate clinical and agricultural fungicide treatments under the "One health" framework applied to Fusarium pathogen control strategies [2].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies on larger population are needed to verify the consistency of this finding. Understanding the evolutionary pressure of environmental fungicides also on clinical isolates may allow to better decipher the mechanisms leading to fungicide adaptation [41]. This can lead to set the most appropriate clinical and agricultural fungicide treatments under the "One health" framework applied to Fusarium pathogen control strategies [2].…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the pathogen showed rapid responses across all major wheat-producing areas to overcome host resistance and gain tolerance to fungicides in less than a decade 10 . Population genomic analyses showed that rapid adaptation of the pathogen was facilitated by parallel evolution across geographic regions 14 , 15 . However, a comprehensive picture of pathogen dispersal and adaptation across the global distribution range is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although loci may be linked for genes which are close together on the same chromosome, resistance of Septoria to some high-risk fungicide classes is conferred by mutations to genes on different chromosomes, leading to independent assortment. For example, resistance to methyl benzimidazoles are caused by mutations to chromosome 1 whereas resistance to succinate dehydrogenase inhibitors can be caused by mutations to chromosome 4, 7 or 8 (Hartmann et al, 2020). The proportion of sexual reproduction between seasons is assumed to be constant, despite evidence that sexual reproduction is influenced by density of infection (Suffert et al, 2018;Eriksen et al, 2001).…”
mentioning
confidence: 99%